EFFICIENCY OF COAGULATION-FLOCCULATION PROCESS IN THE TREATMENT OF ABATTOIR EFFLUENT - FAMILUSI, Ayokunle; ADEKUNLE, Adebola; BADEJO, Adedayo; ADEOSUN, Olayemi (Journal of Engineering Science (Chişinău), 2021)
The use of coagulation-flocculation process as means of wastewater treatment is gradually becoming more popular. This research work is to evaluate the efficiency of coagulation-flocculation process in the treatment of abattoir effluent. Samples of abattoir effluent were collected from a slaughterhouse at Ede, Nigeria, and Alum was used in the coagulation-flocculation treatment of the effluent. The physico-chemical and bacteriological analyses of the untreated and treated effluent were carried out and these were used in determining the efficiency of the treatment process. The values obtained (from the physico-chemical and bacteriological analyses) were also compared with the effluent standard of Environmental Protection Agency (EPA). Coagulation-flocculation process is performed efficiently in reducing the contaminant level of Colour, TDS, Turbidity, Conductivity, TSS, Total Hardness, COD, Coliform, metals and other pollutants from the effluent.